Deficiency of endothelial FGFR1 signaling via upregulation of ROCK2 activity aggravated ALI/ARDS - Deng, Yue; Huang, Xingming; Hu, Yan; Zhong, Weiting; Zhang, Hua; Mo, Chunheng; Wang, Hongjun; Ding, Bi-Sen; Wang, Chen (Frontiers in Immunology, 2023)
Abstract Vascular permeability and inflammation are pathological hallmarks of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). Endothelial cells (ECs) serve as a semipermeable barrier and play a key role in disease progression. It is well known that fibroblast growth factor receptor 1 (FGFR1) is required for maintaining vascular integrity. However, how endothelial FGFR1 functions in ALI/ARDS remains obscure. Here, we revealed that conditional deletion of endothelial FGFR1 aggravated LPS-induced lung injury, including inflammation and vascular leakage. Inhibition of its downstream Rho-associated coiled-coil–forming protein kinase 2 (ROCK2) by AAV Vec-tie shROCK2 or its selective inhibitor TDI01 effectively attenuated inflammation and vascular leakage in a mouse model. In vitro, TNFα-stimulated human umbilical vein endothelial cells (HUVECs) showed decreased FGFR1 expression and increased ROCK2 activity. Furthermore, knockdown of FGFR1 activated ROCK2 and thus promoted higher adhesive properties to inflammatory cells and higher permeability in HUVECs. TDI01 effectively suppressed ROCK2 activity and rescued the endothelial dysfunction. These data demonstrated that the loss of endothelial FGFR1 signaling mediated an increase in ROCK2 activity, which led to an inflammatory response and vascular leakage in vivo and in vitro. Moreover, inhibition of ROCK2 activity by TDI01 provided great value and shed light on clinical translation.